Bioceramic Cements: Supporting in Remineralization of Osteolytic Lesions in Endodontic-periodontal Diseases: A Report of Two Cases - Pereira, Key Fabiano Souza; da Silva , Samara Ortiz; Bastos , Hugo Jose Santos; Tomazinho, Luiz Fernando; Nascimento, Vanessa Rodrigues do; -Verardo, Lia Beatriz Junqueira; Otani, Alex Yoshiharu (Iranian Endodontic Journal, 2023)
Bioceramic cements used for filling root canals in cases of endo-perio lesion of endodontic origin seem to be promising due to having the potential of promoting faster and more predictable healing of the periapical lesion as they stimulate osteogenesis. An effective treatment plan depends on the precise diagnosis of endo-perio lesions. The origin of an infection, being exclusive to the root canal, from the periodontium, or both, is extremely important for devising the treatment plan. In both cases, no clinical evidence of periodontal disease (bleeding, calculus, etc.) was found; however, primary endodontic lesions with the possibility of drainage through the gingival crevice were present. In addition to the disinfection strategies used during the root canal treatments, the bioceramics Bio C Sealer, Bio C Repair and Bio Root RCS were used to fill in the root canals. Both cases presented an impressive bone gain within 8 months for case 1 and 5 months for case 2. Regarding case 1, in the palatal root canal an apical plug with a bioceramic repair cement was used. Based on the literature studied, it can be concluded that after adequate disinfection of the root canals, using bioceramic cements in filling the root canals shows the potential of supporting capabilities in remineralization of osteolytic lesions in endo-perio diseases.